(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Pharmacovigilance is the science and practice of detecting, assessing, understanding, and preventing adverse effects associated with medicines. It plays a crucial role in ensuring that medicines remain safe and effective throughout their lifecycle, from clinical development to post-marketing surveillance. Although clinical trials establish the safety and efficacy of drugs before approval, rare, delayed, or long-term adverse drug reactions (ADRs) may only become evident after widespread use in diverse patient populations. Pharmacovigilance systems collect and analyse ADR reports submitted by healthcare professionals, patients, and pharmaceutical companies to identify potential safety concerns at an early stage. These findings enable regulatory authorities to update prescribing information, introduce safety warnings, restrict the use of certain medicines, or withdraw harmful drugs when necessary. The integration of digital health technologies, electronic reporting systems, artificial intelligence, and global safety databases has significantly improved the efficiency and accuracy of signal detection and risk assessment. Pharmacists play an essential role by encouraging ADR reporting, educating patients on the safe use of medicines, and promoting rational drug therapy. Effective collaboration among healthcare professionals, regulatory agencies, pharmaceutical industries, and patients strengthens pharmacovigilance programmes and enhances public health. Continuous monitoring of medicine safety not only minimizes preventable adverse events but also increases public confidence in healthcare systems. Therefore, pharmacovigilance remains a cornerstone of modern healthcare, ensuring that the benefits of medicines consistently outweigh their risks while supporting the safe and effective use of drugs worldwide.